Morals and manners in Islam a guide to Islamic Adab - Kaysi, Marwan Ibrahim (Islamic Book Trust, 2000)
This compendium of rules regulating Islamic conduct at the personal, familial, social and other levels is a brief yet comprehensive handbook for Muslims and those non-Muslims interested in the Muslim way of life.